Investigating Parents on The Critical Factors Influencing Primary Students’ Continuance Intention To Use Tencent Class Platform in Chongqing, China - Wang, Yixu (Scholar: Human Sciences, 2024)
Purpose: This study aims to explore the factors influencing parents’ continuance intention of the Tencent Class platform among students in a primary school located in Chongqing city, China. The conceptual framework includes variables such as perceived responsiveness, information quality, self-efficacy, service quality, satisfaction, trust, and continuance intention. Research design, data, and methodology: The target population consisted of 500 parents whose children attended Grades 4-6 at Shuren Primary School in China and had experience using the Tencent Class platform. A questionnaire was used as the primary data collection instrument. The study employed judgmental, convenience, and snowball sampling techniques. To ensure the validity and reliability of the questionnaire, the item-objective congruence (IOC) index was utilized for validity testing, while Cronbach’s alpha coefficient was used to assess reliability. The collected data were analyzed using confirmatory factor analysis (CFA) and structural equation modeling (SEM). Results: The study revealed that perceived responsiveness and information quality significantly influenced self-efficacy among parents. Both self-efficacy and service quality had a significant impact on satisfaction, while information quality did not. Furthermore, satisfaction was found to significantly influence continuance intention, mediated by trust. Conclusions: Based on the results, educational institutions and platform providers can take measures to enhance parents’ experience with the Tencent Class platform.